Dynamics of changes in water sectors in patients with alcoholic delirious syndrome - A. G. Sofronov; V. N. Goncharov; V. Y. Skvortsov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2020)
The assessment of fluid distribution in water sectors by the method of integral rheography was carried out in 82 patients who were in the intensive care unit of the psychiatric hospital №3 named after I. I. Skvortsov-Stepanov, about the development of their alcohol delirious syndrome (ALD). As a result of the assessment, rough changes in the water-electrolyte balance and an increase in the content of extracellular fluid were revealed. Since the second day of the patient’s stay in the ICU, there has been a positive dynamics of mental status against the background of complex therapy, including aimed at normalizing the distribution of fluid in both the extracellular and cellular water sectors. Conducted infusion therapy in moderate, negativehydrobalance, was not accompanied by hemodynamicchanges, but led to the resolution of ALD.